Portfólio: desafio de portar mais que folhas: a visão do docente de odontologia - Forte, Franklin Delano Soares; Vieira, Liza Barreto; Pessoa, Talitha Rodrigues Ribeiro Fernandes; Freitas, Claudia Helena Soares Morais; Ferreira, Maria de Lourdes da Silva Marques [UNESP] (FapUNIFESP (SciELO), 2012)
This study aimed to understand professors’ perceptions towards the use of the reflexive portfolio in the area of public health at the UFPB School of Dentistry. The adoption and evaluation of new methodologies were launched by the Program for the Reorientation of Professional Training in Health (Pró- -Saúde). The methodological approach was qualitative, and the data were collected using interviews with professors. The data were processed using the content analysis technique. Two dimensions were identified in use of the portfolio: 1) as a tool for reflection and follow-up of the students’ experiences and 2) an analysis of the fact that this two-year experience reveals the need to continue the records, as a way of expanding the teaching/learning process, beyond the dialogue between professors and students, fostering ties between them. Finally, the professors appreciated the need to improve the portfolio’s use, which has happened gradually each semester, contributing actively to the development of more reflexive and critical professionals, orienting students’ self-evaluation and fostering their autonomy.

O objetivo deste trabalho foi compreender a concepção dos docentes da área de Saúde Coletiva do curso de Odontologia da UFPB no uso do portfólio reflexivo. A adoção de novas abordagens metodológicas e consequente avaliação desses processos foram disparadas pelo Programa de Reorientação da Formação dos Profissionais em Saúde (Pró-Saúde). A abordagem qualitativa foi a opção metodológica, e os dados foram coletados por meio de entrevistas com os docentes. A análise dos dados foi realizada a partir da técnica de análise do conteúdo. Constataram-se duas dimensões do uso do portfólio. A primeira diz respeito ao seu uso como ferramenta de reflexão e acompanhamento das vivências dos estudantes. A segunda trata do fato de que essa experiência nesses dois anos reflete a necessidade de continuação dos registros, pois é uma forma de ampliar o processo de ensino-aprendizagem, além do diálogo entre professores e estudantes, oferecendo a criação de vínculo. Por fim, os docentes compreendem que é preciso o aprimoramento da aplicação do portfólio, o que tem acontecido de maneira gradual a cada semestre, contribuindo ativamente para a construção de profissionais mais reflexivos, críticos, norteando a autoavaliação e trabalhando a autonomia do estudante.
The portfolio system and the challenge of carrying more than classroom notes: the view of a dentistry professor
Keywords: Education; Reflexive portfolio; Formative evaluation; Teaching-learning methodology; Formação; Portfólio reflexivo; Avaliação formativa; Metodologias de ensino-aprendizagem